A critical review on correlating active sites, oxidative species and degradation routes with persulfate-based antibiotics oxidation - Li, Ning; Ye, Jingya; Dai, Haoxi; Shao, Penghui; Liang, Lan; Kong, Lingchao; Yan, Beibei; Chen, Guanyi; Duan, Xiaoguang (Water research (Oxford), 2023)
•PS activation by heterogeneous catalysts are compared systematically.•The relationship between active sites and oxidative species is summarized.•The information of reactive species acting on antibiotics is discussed.•The generation and function of radical and non-radicals are compared. At present, numerous heterogeneous catalysts have been synthesized to activate persulfate (PS) and produce various reactive species for antibiotic degradation from water. However, the systematic summary of the correlation among catalyst active sites, PS activation pathway and pollutant degradation has not been reported. This review summarized the effect of metal-based, carbon-based and metal-carbon composite catalysts on the degradation of antibiotics by activating PS. Metal and non-metal sites are conducive to inducing different oxidation pathways (SO4•−, •OH radical oxidation and 1O2 oxidation, mediated electron transfer, surface-bound reactive complexes and high-valent metal oxidation). SO4•− and •OH are easy to attack CH, S-N, CN bonds, CC double bonds and amino groups in antibiotics. 1O2 is more selective to the structure of the aniline ring and amino group, and also to attacking CS, CN and CH bonds. Surface-bound active species can cleave CC, SN, CS and CN bonds. Other non-radical pathways may also induce different antibiotic degradation routes due to differences in oxidation potential and electronic properties. This critical review clarified the functions of active sites in producing different reactive species for selective oxidation of antibiotics via featured pathways. The outcomes will provide valuable guidance of oriented-regulation of active sites in heterogeneous catalysts to produce on-demand reactive species toward high-efficiency removing antibiotics from water. [Display omitted]